The value of private sector business credit information sharing: The US case - Kallberg, Jarl G; Udell, Gregory F (Journal of Banking & Finance, 2003)
This paper investigates the value added by private information exchanges that share information on business payment performance. We discuss how this information is collected and disseminated by the world’s largest private information broker, Dun & Bradstreet. We provide the first empirical examination of the importance of this information at the lending decision level. Our findings indicate that exchange-generated information provides significant explanatory power in failure prediction models controlling for other credit information that is easily available to lenders. Our study complements the work of Jappelli and Pagano [Information sharing, lending and defaults; Cross country evidence, Centre for Economic Policy Research, Discussion Paper 2184, 1999] who find in cross-country macro level tests that information exchanges add value.